Advancements in Ocular Therapy: A Review of Emerging Drug Delivery Approaches and Pharmaceutical Technologies - Bhupendra Raj Giri; Deeksha Jakka; Michael A. Sandoval; Vineet R. Kulkarni; Quanying Bao (MDPI AG, 2024)
Eye disorders affect a substantial portion of the global population, yet the availability of efficacious ophthalmic drug products remains limited. This can be partly ascribed to a number of factors: (1) inadequate understanding of physiological barriers, treatment strategies, drug and polymer properties, and delivery systems; (2) challenges in effectively delivering drugs to the anterior and posterior segments of the eye due to anatomical and physiological constraints; and (3) manufacturing and regulatory hurdles in ocular drug product development. The present review discusses innovative ocular delivery and treatments, encompassing implants, liposomes, nanoparticles, nanomicelles, microparticles, iontophoresis, in situ gels, contact lenses, microneedles, hydrogels, bispecific antibodies, and gene delivery strategies. Furthermore, this review also introduces advanced manufacturing technologies such as 3D printing and hot-melt extrusion (HME), aimed at improving bioavailability, reducing therapeutic dosages and side effects, facilitating the design of personalized ophthalmic dosage forms, as well as enhancing patient compliance. This comprehensive review lastly offers insights into digital healthcare, market trends, and industry and regulatory perspectives pertaining to ocular product development.